Pentingnya Kualitas Pelayanan dalam Anuitas dengan Tinjauan Financial Highlight Asuransi di PT. Asuransi Umum Bumiputera Muda 1967 Cabang Medan - Handayani, Oktavia; Sari, Maya; Nopiazinda, Adelia; Anugrah, Rizki; Rahayu, Sri Ulfa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The Importance of Service Quality in Annuities with a Review of Financial Highlights of Insurance at PT. Bumida General Insurance 1967. This research focuses on the importance of service quality in the annuity products offered by PT. Bumida General Insurance 1967. By combining qualitative and quantitative approaches, this study evaluates how service quality affects customer perceptions and company financial performance. The findings show that superior service quality plays an important role in increasing customer confidence and strengthening the company's financial position in the insurance sector. The data analysis technique used is the data triangulation technique, namely testing similar data from various sources. Based on the results of these observations, it appears that the quality of customer service at Bumida General Insurance 1967 Medan Insurance branch is quite good. This is demonstrated by the absence of complaints from customers who remain and do not move to other service companies or insurance companies. Bumida 1967 continues to survive in world competition even though many other insurance companies have emerged that are no less large. Currently, Asuransu Bumida 1967 is still one of the largest insurance companies in Indonesia. However, the quality of service at the Bumida Bersama Life Insurance Medan branch must continue to be improved so that the positive image that has been created can be maintained.